A covalent deprotection strategy for assembling supramolecular coordination polymers from metal–organic cages. Issue 85 (30th September 2020) - Schneider, Matthew L.; Linder-Patton, Oliver M.; Bloch, Witold M.
Abstract : A covalent deprotection strategy facilitates the self-polymerisation of amine-functionalised Cu4 L4 metal–organic cages into supramolecular coordination polymers with tunable porosity. Abstract : A Cu4 L4 metal–organic cage (MOC) composed of amine-protected ligands forms supramolecular coordination polymers (SCPs) upon covalent post-assembly deprotection. The amorphous SCPs form by virtue of aniline–copper coordination and possess a tunable porosity based on the rate of deprotection.